The Lipid Metabolic Landscape of Cancers and New Therapeutic Perspectives - Wang, Wenjun; Bai, Ling; Li, Wei; Cui, Jiuwei (Frontiers in Oncology, 2020)
Lipid metabolism reprograming, as a hallmark of malignancy, has received renewed interest in recent years in such areas as energy sources, cell membrane components, and signaling molecules involved in the rapid tumor growth and the adaptation to the tumor microenvironment. Lipid metabolism deregulation in cancer involves multiple aspects, including an increased lipid uptake, endogenous de novo fatty acid synthesis, fatty acid oxidation, and cholesterol accumulation, thereby promoting tumor growth and progression. Recent advances in the understanding of specific metabolic alterations in cancer reveal novel pathogenesis mechanisms and a growing number of drugs targeting lipid metabolism have been applied in anti-tumor therapy. Thus, this review discusses the lipid metabolic landscape of cancers and the interplay with oncogenic signaling, and summarizes potential therapeutic targets to improve the therapeutic efficiency in cancer patients, in order to provide more reference and thinking for the treatment of lipid metabolism of cancer patients.